Peran Media Sosial Dalam Berdakwah - Ali Sodikin; Solikhah Solikhah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2022)
This study aims to find out how the role of social media in preaching with the @obyrezapost Instagram account. The research method used is a descriptive method with a qualitative approach. Data collection techniques with the method of observation, interviews and documentation. The data obtained were then analyzed by data reduction, data presentation and drawing conclusions. The results of this study indicate that the role of Instagram as a propaganda medium for the @obyrezapost Instagram account can be seen from how Oby Reza as the account owner uses Instagram as a propaganda medium. Oby Reza always inserts da'wah messages in each of his uploads in the form of photos and videos that have been edited as attractively as possible. Using every feature provided by Instagram to attract the attention of followers and other users.